2008
DOI: 10.1063/1.2990767
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the bond-angle dispersion by Raman spectroscopy and the strain energy of amorphous silicon

Abstract: A thorough critical analysis of the theoretical relationships between the bond-angle dispersion in a-Si,⌬ , and the width of the transverse optical Raman peak, ⌫, is presented. It is shown that the discrepancies between them are drastically reduced when unified definitions for ⌬ and ⌫ are used. This reduced dispersion in the predicted values of ⌬ together with the broad agreement with the scarce direct determinations of ⌬ is then used to analyze the strain energy in partially relaxed pure a-Si. It is concluded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In this case, the epitaxial crystallization rate of a 2 µm thick amorphous region obtained by ion implantation on a c-Si wafer remained essentially the same (within an error bar of 3%) before and after partial structural relaxation. From the Raman spectra of that sample, we can estimate [36] that the crystallization enthalpy diminished from 812 to 605 J g −1 (i.e., by 60 meV/atom) due to structural relaxation.…”
Section: Experimental Results For A-simentioning
confidence: 99%
“…In this case, the epitaxial crystallization rate of a 2 µm thick amorphous region obtained by ion implantation on a c-Si wafer remained essentially the same (within an error bar of 3%) before and after partial structural relaxation. From the Raman spectra of that sample, we can estimate [36] that the crystallization enthalpy diminished from 812 to 605 J g −1 (i.e., by 60 meV/atom) due to structural relaxation.…”
Section: Experimental Results For A-simentioning
confidence: 99%
“…To minimize the influence of the weak vibrational modes, LA and LO, one can perform a best fit on each spectrum from 250 to 550 cm −1 by three Gaussian curves and a straight base line [24]. The RMS bond angle deviation was deduced using the following formula, proposed by Beeman et al [27,28]. Figure 3 shows the TO peak position and δθ change during light-soaking.…”
Section: In-situ Raman Studiesmentioning
confidence: 99%
“…Recently, we have shown that before crystallization begins, structural relaxation processes stop near 8.7°because most of the mobile defects, whose diffusion facilitates network restructuring, have already recombined. 3,5 This conclusion leaves the door open to the possibility of reaching a higher degree of relaxation if alternative mechanisms for network restructuring were to come into play. In that case, further diminution of ⌬ would be possible and, eventually, a value of ⌬ below 6.6°could be reached if the real minimum value of ⌬ were lower than predicted.…”
mentioning
confidence: 99%